2020
DOI: 10.1055/a-1107-3025
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Presentation After Concussion and Pre-existing Anxiety Among Youth Athletes

Abstract: Our purpose was to evaluate the effect of self-reported pre-injury anxiety diagnosis on persistent symptom development, vestibular symptom severity, and balance control among youth who sustained a concussion. We performed a retrospective study of patients seen at a specialty pediatric concussion clinic. Patients were 18 years of age or younger, examined within 10 days of concussion, and received care until full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Moreover, in a large-scale study of youth receiving care in concussion specialty clinics, pre-existing anxiety disorders were associated with more severe symptomology and prolonged recovery in children and adolescents (11). However, Kent et al (12) reported that a pre-existing anxiety diagnosis was not associated with persistent symptoms after concussion, after adjusting for sex and a personal history of migraine, depression, and attentiondeficit/hyperactivity disorder (ADHD). Thus, several, but not all, studies to date suggest that pre-injury anxiety is important to consider during the medical management of youth who sustain concussions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a large-scale study of youth receiving care in concussion specialty clinics, pre-existing anxiety disorders were associated with more severe symptomology and prolonged recovery in children and adolescents (11). However, Kent et al (12) reported that a pre-existing anxiety diagnosis was not associated with persistent symptoms after concussion, after adjusting for sex and a personal history of migraine, depression, and attentiondeficit/hyperactivity disorder (ADHD). Thus, several, but not all, studies to date suggest that pre-injury anxiety is important to consider during the medical management of youth who sustain concussions.…”
Section: Introductionmentioning
confidence: 99%